Penerapan Pendekatan Keterampilan Proses Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas IV di SD Negeri 18 Rejang Lebong - Elyana Elyana (AR-RIAYAH: Jurnal Pendidikan Dasar)
This research is grounded by the lack of developing of learning strategy and the low of the result of the learning of the students especially for the scients subject.This research is the classroom action research that have been done in SDN 18 Rejang Lebong, class IV with 24 students. This research know that the first the medium score in students observation cycle I is 17 its an enough category, for cycle II the medium score is 19 its a good category and cycle III with the medium score 23 its a best category. The medium score for the teacher observation in cycle I is 19 its an enough category, cycle II, the medium is 22 its a good category and increase in cycle III with the medium score 25,5 its a best category. The second, in cycle I finishing the classical of the students is 50 %, cycle II finishing of the classical learning students is 75 % and cycle III, finishing classical learning is 100 %. Its suggested for the teacher in applyng skill process. Without guiding and pointing from the teacher it would’nt create well skill process.